Respectus Philologicus, 2011 Nr. 20 (25) - Bankauskaitė, Gabija (Respectus Philologicus, 2011)
CONTENTS I. PROBLEMS AND SOLUTIONS Loreta Ulvydienė, Giedrė Drėgvaitė (Lithuania). Linguistic Experience as the Projection of Urban Cognition in Literature...11 Saule Altybayeva (Kazakhstan). Neomythologism of the Modern Kazakh Prose: Polycultural Discourse and Art Prospect Search...27 Michał Mazurkiewicz (Poland). The Nature of Ritual... 40 II. FACTS AND REFLECTIONS Laima Kalėdienė (Lithuania). Attitude Towards the Official Language According to the Data of Sociolinguistic Survey... 52 Vadim V. Dementyev (Russia). Glamour as “The Old New Svetskost”?....65 Elena Bonta, Raluca Galiţa (Rumunia). Joking as a Semiotic Practice and Means of Spiritual Survival. A Pragma-linguistic and Stylistic Approach... 80 Irina Melnikova (Lithuania). The Gorris Defence, Or Nabokov on Screen... 95 Jadvyga Krūminienė, Artūras Cechanovičius (Lithuania). On some Jungian Archetypes Reflected in Joseph Conrad’s Heart of Darkness... 107 Ewa Anna Piasta (Poland). Axiological Horizons of the Short Story „The Dream of the Saint“ by Reinhold Schneider... 122 Oleg N. Grinbaum (Russia). The Fourth Chapter of the Novel “Eugene Onegin” by A. S. Pushkin: Onegin’s Monologue in the Light of Rhythm and Meaning ... 133 Valentina Litvinova (Russia). The Epistolary Heritage of A. Chekhov from Siberia (the Letters of the Writer from the Point of View of Time and Space)... 153 Roma Konsevičiūtė (Lithuania). The “Giesmių Giesmė” (The “Song of Songs”) Motive Transformation in Antanas Jasmantas’ Lyrics... 162 Eleonora Lassan (Lithuania). Conjunction зато as a Means of Realization of Psychological Compensation in the Russian Language.... 170 Joanna Senderska (Poland). The Social Vocabulary Enrichment Based on Selected Cases of Polish Sociolects...181 Danguolė Melnikienė (Lithuania). Peculiarities of the Specific Realia Expression in Lithuanian Bilingual Dictionaries... 192 Marlena Chudzik (Poland). Toponomastic Scholars’ Problems... 202 Daiva Aliūkaitė (Lithuania). Expression Ideals of Young Samogitians: Conscious Attitude...209 Yuri Tambovtsev, Ludmila Tambovtseva, Juliana Tambovtseva (Rusija / Rosja). Functioning of the Continuous Tenses in Female and Male Variants of the American and British English Language...221 Natalia Krasilnikova (Russia). Public Opinion in the Light of Cognitive Discourse Paradigm... 233 III. OPINION Jelena Konickaja, Artur Zapolskij (Lithuania). Metaphors in Lithuanian and Slovenian Political Discourse... 243 IV. SCIENTIFIC LIFE CHRONICLE Conferences Viktorija Makarova (Lithuania). “Language and Method”. Krakow, 5–6 May, 2011...254 Daiva Aliūkaitė (Lithuania). Project “Research on Modern Geolinguistics in Lithuania: Point Network Optimization and Dissemination of Interactive Dialect Information“...257 Books reviews Danutė Balšaitytė (Lithuania). Diagnosed. What next? ЛАССАН, Э., 2011. Лингвистика ставит диагноз... Очерк «духа эпохи» в свете данных лингвистического анализа... 260 Dagnė Beržaitė (Lithuania). Remarks of Ungrateful Reader. DOSTOJEVSKIS, F., 2010. Apysakos I: Antrininkas, Žiemos pastabos apie vasaros įspūdžius, Užrašai iš pogrindžio... 267 Announce... 271 V. REQUIREMENTS FOR PUBLICATION...272 VI. OUR AUTHORS...280